SPA resistant elliptic curve cryptosystem using addition chains. (15th October 2007) - Byrne, Andrew; Crowe, Francis; Marnane, William Peter; Meloni, Nicolas; Tisserand, Arnaud; Popovici, Emanuel
There has been a lot of interest in recent years in the problems faced by cryptosystems due to side channel attacks. Algorithms for elliptic curve point scalar multiplication such as the double-and-add method are prone to such attacks. By making use of special addition chains, it is possible to implement a Simple Power Analysis (SPA) resistant cryptosystem. In this paper, a reconfigurable architecture for a cryptographic processor is presented. A SPA resistant algorithm for point multiplication is implemented and is shown to be faster than the double-and-add method. Post place and route results for the processor are given.